Child-Friendly Justice – Serbian Perspective - S. Knežević, Marko (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract: The UN Convention on the Rights of the Child (CRC) was ratified by Serbia in 1991, but the specific rights of children to participate in court proceedings were more clearly defined with the Family Act of 2005. Serbian law establishes a strong foundation for child-friendly justice, aligning closely with CRC obligations. Children capable of forming opinions have the right to express them in court proceedings relevant to them, with no age threshold for such fundamental judicial participation right. Court accessibility in all procedures is governed by the principle of the child’s best interests. Special regulations exist particularly for criminal cases involving juvenile offenders and minors who are victims, prioritising children’s interests. Nonetheless, challenges remain in effectively implementing these normative frameworks to achieve a truly child-friendly justice system. Keywords: participation rights of children in Serbian law, child’s right to be heard in Serbian court proceedings, access to the court proceedings in Serbian Law, child-friendly justice in Serbia